The cow GUTBIOME CY study: investigating the composition of the cattle gut microbiome in health and infectious disease transmission in cyprus - Daphne E. Mavrides; Maria Liapi; Despo Ierodiakonou; Christodoulos Pipis; Stavros Malas; Eleni Gentekaki; Anastasios D. Tsaousis (BMC Veterinary Research)
Abstract Background Recent evidence suggests that the lower gut microbiome of ruminants presents roles in their health and environment, including the development of the mucosal immune system, milk production efficiency and quality and subsequent methane emissions. However, there are proportionately fewer studies on this complex microbial community in cattle and region-focus studies are non- existent. Methods Herein, we present the research protocol of the GUTBIOME CY project pertaining to determine the composition of the lower gut microbiome in dairy cows situated in 37 farms across five districts of the island of Cyprus. Detailed questionnaires on animal husbandry and farming practices will be gathered from each farm. Faecal, milk (individual and bulk) and water samples will also be collected from cows and their offspring. Samples will be analysed using a combination of molecular biology and bioinformatics pipelines to define microbiome profiles and antimicrobial resistance (AMR). Information collected from the questionnaires will be used to test for associations between animal husbandry or farming practices and microbiome components and AMR. Discussion Collected samples will establish the first dairy cattle biobank in the country for contributing substantially towards scientific advancements in microbiome research and providing insights to all stakeholders, tailored to the unique agricultural context of Cyprus.